Cascade of the Hinsberg / IMDAF reactions in the synthesis 2-arylsulfonyl-3a, 6-epoxyisoindoles and 4a, 7-epoxyisoquinolines in water. (9th April 2021) - Nadirova, Maryana A.; Khanova, Anastasia V.; Zubkov, Fedor I.; Mertsalov, Dmitriy F.; Kolesnik, Irina A.; Petkevich, Sergey K.; Potkin, Vladimir I.; Shetnev, Anton A.; Presnukhina, Sofia I.; Sinelshchikova, Anna A.; Grigoriev, Mikhail S.; Zaytsev, Vladimir P.
Abstract: N -Furfuryl allylamines, readily accessible from corresponding furfurals or furfuryl amines, react with a broad range of arylsulfonyl chlorides with the formation of a 3a, 6-epoxyisoindole core in one synthetic stage. Usually, in boiling water, the interaction sequence involves two consecutive steps: the Hinsberg reaction and the intramolecular Diels–Alder furanе (IMDAF) reaction. The scope and limitations of the proposed method were thoroughly investigated, and it was revealed that the key [4 + 2] cycloaddition step proceeds through an exo -transition state, giving rise to the exclusive formation of a single diastereomer of the target heterocycle. The method allows the ability to obtain N -sulfaryl-substituted 3a, 6-epoxyisoindoles and 4a, 7-epoxyisoquinolines, which are potentially useful substrates for further transformations and subsequent bioscreening, in particular antimicrobial activity. Graphical abstract: Image 1 Highlights: A short IMDAF strategy to give 2-(arylsulfonyl)-3a, 6-epoxyisoindoles from readily available initial materials was proposed. Cascade of the Hinsberg / IMDAF Reactions is very simple and strongly depends on the characteristics of substituents. Aforesaid epoxyisoindoles possess antibacterial activity against gram-negative or gram-positive sensitive bacteria strains.